A simple flashcard: big impact for junior doctors!. (October 2014) - Rutkowski, David; Keelan, Ray; Warrander, Lynne; Steinke, Douglas
Summary Background Reducing prescribing errors is key to ensuring patient safety. Foundation‐year doctors (FYs) have been found to be major contributors to prescribing errors, and often feel poorly prepared for prescribing by their undergraduate education. Numerous studies have reported these findings; however, few studies have introduced meaningful interventions. Methods A questionnaire was sent to FY2s (n = 20) to determine the 15 most commonly prescribed medications on call. These medications and instructions were incorporated into a flashcard that was disseminated to new FY1s at a teaching hospital in the UK. The FY1s were asked to complete a pre‐ and post‐flashcard questionnaire, giving instructions for 10 medications and their confidence in prescribing these medications. A control group at another teaching hospital were given the same questionnaires, but not the flashcard. Results No significant difference in confidence was seen in FY1s at either hospital before the flashcard was issued. Both groups at week 4 demonstrated significant improvements in confidence in prescribing, with those who received the flashcard demonstrating a significantly higher level of confidence in a greater range of medications, compared with those who did not (p < 0.05). At week 4, 93 per cent of FY1s still used the flashcard 2.2 times per day, claiming that it saved time on call (9.2/10). Discussion We have introduced an inexpensive and simple prescribing aid, which has been statistically shown to improve prescribing confidence in FY1s. <boxed-text content-type="pullQuote" position="anchor" orientation="portrait"> Foundation‐year doctors have been found to be major contributors to prescribing errors </boxed-text>